Centro Internacional de Arte e Cultura Humanista Recanto Maestro/RS- Brasil: uma proposta para solicitação da Chancela Paisagem Cultural? - Dallepiane, Bruna Marquetti (2017)
This work investigates the possibility of qualifying the Recanto Maestro Humanist International Art and Culture Center as a possible candidate to obtain the Cultural Landscape Chancela. The methodology of the research was a qualitative approach carried out through a case study. As sources of research, we seek historical documents, photographs, charts, maps, legal documents and interviews with institutions interested in preserving the local heritage, as well as people who could report facts reconstructing the historical and cultural scenario to elaborate the application dossier of the chancela. The product of this research was a dossier that presents a proposal to chancela to the District Recanto Maestro, composed of a Management Pact to be signed between institutions interested in safeguarding the equity. This document has the guidelines for urban development, site history, landscape detailing and architecture. This set of elements makes that Recanto Maestro can be considered a peculiar part of the national territory, being thus qualified for the chancela.